World Bank Group And International Monetary Fund Support For Debt Relief Under The Common Framework And Beyond. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
This paper discusses World Bank and IMF support for addressing fiscal and debt distress in IDA countries, with emphasis on strong continued concessional flows for green, resilient, and inclusive development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet